2017
DOI: 10.18632/oncotarget.21970
|View full text |Cite
|
Sign up to set email alerts
|

Functions of pancreatic stellate cell-derived soluble factors in the microenvironment of pancreatic ductal carcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal forms of cancer with poor prognosis because it is highly resistant to traditional chemotherapy and radiotherapy and it has a low rate of surgical resection eligibility. Pancreatic stellate cells (PSC) have become a research hotspot in recent years, and play a vital role in PDAC microenvironment by secreting soluble factors such as transforming growth factor β, interleukin-6, stromal cell-derived factor-1, hepatocyte growth factor and galectin-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 154 publications
(164 reference statements)
2
41
0
Order By: Relevance
“…Another hallmark of PDAC tumors is an extremely immunosuppressive microenvironment. Numerous studies have confirmed a major role for CAFs in generating factors, such as secreted cytokines and chemokines (Harper and Sainson, 2014;Wu et al, 2017), that contribute to this environment, as well as physically sequestering anti-tumor immune cells (Ene-Obong et al, 2013). Furthermore, compared to many other tumor types, PDAC has one of the lowest mutational burdens and display of neoantigens (Chalmers et al, 2017;Evans et al, 2016), which correlates directly with low response rates to immune checkpoint inhibitors, such as PD-1 (Yarchoan et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another hallmark of PDAC tumors is an extremely immunosuppressive microenvironment. Numerous studies have confirmed a major role for CAFs in generating factors, such as secreted cytokines and chemokines (Harper and Sainson, 2014;Wu et al, 2017), that contribute to this environment, as well as physically sequestering anti-tumor immune cells (Ene-Obong et al, 2013). Furthermore, compared to many other tumor types, PDAC has one of the lowest mutational burdens and display of neoantigens (Chalmers et al, 2017;Evans et al, 2016), which correlates directly with low response rates to immune checkpoint inhibitors, such as PD-1 (Yarchoan et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the metabolic roles, CAFs are also at the center of the immunosuppressive PDAC microenvironment (Basso et al, 2014;Clark et al, 2007;Fu et al, 2018;Harper and Sainson, 2014). CAFs exert immunosuppressive effects through direct modulation of immune cell function via cytokine secretion (Wu et al, 2017), exclusion of anti-tumor immune cells from the tumor (Ene-Obong et al, 2013), and/or recruitment of immunosuppressive immune cells to the tumor (Kumar et al, 2017). Intriguingly, recent studies have reported a functional link between metabolism and immune cell function, which has suggested that anti-tumor immune cells rely on a constant supply of nutrients to perform their functions (Buck et al, 2017;Kouidhi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Activated PSCs are classified as a loss of cytoplastic lipid droplets, upregulation of MMP and ECM proteins [ 37 ], and activated PSCs acquire proliferative capacity. Additionally, activated PSCs play a vital role in the pancreatic cancer microenvironment by secreting molecules such as TGFβ, IL-6, stromal cell-derived factor-1 (SDF-1), hepatocyte growth factor (HGF) and galectin-1 to promote pancreatic cancer progression [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the cellular interactions taking place between the cancer and stroma has recently emerged as an important topic in pancreatic cancer research [43][44][45]. Multiple new stromal targets of potential clinical importance in PDAC are currently being investigated [46].…”
Section: Discussionmentioning
confidence: 99%